2017
DOI: 10.3389/fphar.2017.00521
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Understanding of Protein-Protein Interactions in Drug Metabolizing Enzymes through the Use of Biophysical Techniques

Abstract: In recent years, a growing appreciation has developed for the importance of protein-protein interactions to modulate the function of drug metabolizing enzymes. Accompanied with this appreciation, new methods and technologies have been designed for analyzing protein-protein interactions both in vitro and in vivo. These technologies have been applied to several classes of drug metabolizing enzymes, including: cytochrome P450's (CYPs), monoamine oxidases (MAOs), UDP-glucuronosyltransferases (UGTs), glutathione S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 123 publications
(170 reference statements)
0
8
0
Order By: Relevance
“…Both Cyp1a2 and Cyp2e1 proteins bind Pgrmc1, and the proteins are expressed at lower levels in Pgrmc1 KO liver. PGRMC1 most likely controls enzyme activity by stabilizing cytochromes P450 rather than affecting the catalytic cycle of the enzyme, but a concomitant effect on the k cat of cytochromes P450 upon PGRMC1 binding cannot be ruled out as protein–protein interactions are also known to alter cytochrome P450 activity ( 39 , 40 , 41 , 42 ). Evidence exists that PGRMC1 binds cytochromes P450 directly.…”
Section: Discussionmentioning
confidence: 99%
“…Both Cyp1a2 and Cyp2e1 proteins bind Pgrmc1, and the proteins are expressed at lower levels in Pgrmc1 KO liver. PGRMC1 most likely controls enzyme activity by stabilizing cytochromes P450 rather than affecting the catalytic cycle of the enzyme, but a concomitant effect on the k cat of cytochromes P450 upon PGRMC1 binding cannot be ruled out as protein–protein interactions are also known to alter cytochrome P450 activity ( 39 , 40 , 41 , 42 ). Evidence exists that PGRMC1 binds cytochromes P450 directly.…”
Section: Discussionmentioning
confidence: 99%
“…Allosteric receptor-receptor interaction, which is still an underexplored mechanism of receptor modulation [37], has been suggested to be an especially effective approach to control NMDA receptor function [38][39][40]. The functional readout from the interaction between two proteins is often modified by small molecules [41,42], and it is well established that ouabain binding to the potassium-binding state of the catalytic NKA subunit changes its conformation [43][44][45]. Lack of effect of the low ouabain concentration on membrane potential (Supp.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying protein interaction sites and uncovering the interaction mechanism is closely relevant in the drug development industry. In addition, unveiling of protein interaction partners allows biologists to construct protein interaction networks, which in turn facilitate the understanding of many biological and clinical observations [ 19 , 20 , 21 , 22 ]. The data in this study indicated that Tb -DdlA could not maintain its activity long in vitro under the conditions tested, which might be attributable to its synergistic effect with potential interacting proteins that stabilized its activity in vivo.…”
Section: Discussionmentioning
confidence: 99%